Steps of learning strategies in social science learning activities - Irwan Satria (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
This study aims to determine the learning strategy implementation that is applied in social science learning activities at MIN 2 Bengkulu City “as a representative, purposive and inspirational sample. This is due to a number of reasons, such as in social science learning activities at the basic education level only using teacher-centered expository learning strategies. In addition, the teacher is not right in selecting, sorting, and implementing learning strategies. The lack of variety in learning methods increasingly makes students less/less versed in the subject matter. In the end, with fewer/not mastering students in social science subjects, the learning outcomes/grades are poor. The research method used is field research with a qualitative descriptive approach. The results of this study in the form of implementing learning strategies in learning activities in the field of social science are generally divided into three steps, namely planning; time, sequence of learning activities, methods, media/learning materials, implementation; preliminary activities, core activities and closing activities and follow-up and end with evaluation; test and non-test. The learning strategies used in learning social sciences are reading aloud, active sharing of knowledge, and small group discussions.